The Effect of Price and Service Quality On Buying Interest In Three-Brother Gallon Water - Apriansyah, Roky; Hermanto, Hermanto; Ningsih, Fitria; Hairudin, Abdul; Afriaris, Said (Devotion : Journal of Research and Community Service, 2022)
The study was conducted on the refillable water of three brothers. Consumers ' buying interest in three   brothers' refillable water has decreased every year, this is due to the price offered is still less competitive with competitors who sell The same product and the quality of service that is felt is still not suitable by consumers, thus consumers move to other places.  The research uses a quantitative approach with primary data. The number of samples is 100 people, random sampling with accidental sampling.   The results showed that the price  and quality of service simultaneously  affected  consumers  ' buying interest in the  refillable water  of the  three brothers,  the  price partially affected the consumers' buying interest in three brothers' refillable water  and  the quality of service partially  affect consumers'  buying interest in  three  brothers' refillable water.